Capturing the Multi-Dimensionality of Energy Access - Bhatia, Mikul; Angelou, Nicolina (World Bank, Washington, DC, 2014)
There are two initial challenges in defining and measuring energy access: the absence of a universal definition of energy access and the difficulty of measuring any definition in an accurate manner. The multi-tier approach to measuring energy access proposed in the Sustainable Energy for All (SE4ALL) Global Tracking Framework of 2013 introduces a five-tier measurement methodology based on various energy attributes, such as quantity, quality, affordability, and duration of supply. The approach makes it possible to compute a weighted index of access to energy for a given geographical area. Separate notes focus on multi-tier measurement of energy access for households, productive enterprises, and community institutions. The type of data required for a multi-tiered assessment of energy access in a given area can be obtained through surveys of actual energy availability and use among a scientific sample of all users in a given category (households, enterprises, community institutions). Survey questionnaires elicit information about each energy attribute, and the results are fed into the multi-tier matrices. Data may also be collected from energy suppliers to indicate the tiers of access that specific projects may deliver to a targeted population. Capturing the multi-dimensionality of energy access is important, because rapid expansion of access to energy requires both accurate assessment and tracking of progress. Under the new multi-tier framework, data from energy surveys are compiled and analyzed to produce an energy access diagnostic for a given area. The diagnostic includes an in-depth disaggregated data analysis and an aggregate analysis comprising a series of indices of energy access. Defining and measuring energy access by considering attributes of energy supply yields a better understanding of how various interventions improve access.